APPROACHES TO FOSTER LEARNER AUTONOMY IN EFL LEARNING: A LITERATURE REVIEW - Daflizar (Journey: Journal of English Language and Pedagogy, 2023)
Learner autonomy has been a major topic of research in foreign language education for a long time. Despite the prevalent consensus that learner autonomy is concerned with a learner’s capacity to take control or take charge of his/her own learning (Benson, 2013), this does not mean that the teacher’s role is unnecessary. In recent years, many approaches to promoting learner autonomy have been suggested and many empirical studies have been carried out to examine the effectiveness of the approaches. This paper aimed at reviewing approaches to promoting learner autonomy. First, the definitions of learner autonomy are presented, followed by a discussion of the teacher’s roles in promoting learner autonomy. Next, six approaches to fostering learner autonomy as proposed by Benson (2001) are reviewed with references to both theories and results of empirical research. Based on the review, it can be concluded that teachers play an important role in the development of learner autonomy, and although the six approaches have different emphases, they seem to have more similarities than differences, particularly in encouraging learners to plan and follow their language learning paths to attain their goals. Implications for future research are put forward.